Hypoxia-inducible factor-1α promotes macrophage functional activities in protecting hypoxia-tolerant large yellow croaker (Larimichthys crocea) against Aeromonas hydrophila infection - Zhang, Yibo; Wang, Xuelei; Gao, Zhenyu; Li, XuJie; Meng, Ran; Wu, Xiongfei; Ding, Jie; Shen, Weiliang; Zhu, Junquan (Frontiers in Immunology, 2024)
The immune system requires a high energy expenditure to resist pathogen invasion. Macrophages undergo metabolic reprogramming to meet these energy requirements and immunologic activity, polarize to M1 type macrophages. Understanding the metabolic pathway switching in large yellow croaker (Larimichthys crocea) macrophages in response to lipopolysaccharide (LPS) stimulation and whether this switching affects immunity is helpful to explain the stronger immunity of hypoxia-tolerant L. crocea). In this study, transcript levels of glycolytic pathway genes (Glut1, Pdk1), mRNA levels or enzyme activities of glycolytic enzymes (HK, PFK, PK, LDHA), aerobic respiratory enzymes (PDH, IDH, SDH), metabolites (LA, ATP), levels of bactericidal products (ROS, NO), and transcripts and level changes of inflammatory factors (IL1β, TNFα, IFNγ) were detected in LPS-stimulated L. crocea head kidney macrophages. We showed that glycolysis was significantly induced, the tricarboxylic acid (TCA) cycle was inhibited, and metabolic reprogramming occurred, showing the Warburg effect when immune cells were activated. To determine the potential regulatory mechanism behind these changes, LcHIF-1α was detected, and found to be significantly induced and transferred to the nucleus after LPS stimulation. LcHif-1α interference led to significantly reduced of glycolytic pathway gene transcripts expression, enzyme activity, metabolites, bactericidal substances and inflammatory factor levels, a significant increase in the aerobic respiration enzymes, and decreased migration, invasion and phagocytosis. Further ultrastructural observation by electron microscope showed the fewer microspheres contained phagocyte and more cell damaged after LcHif-1α interference. LcHif-1α overexpression L. crocea head kidney macrophages showed the opposite trend, and promoter activities of Ldha and Il1β were significantly enhanced after LcHif-1α overexpression in HEK293T cells. Our data showed that the LcHIF-1α acted as a metabolic switch in L. crocea macrophages and was important in polarization. Hypoxia-tolerant L. crocea head kidney showed a stronger Warburg effect and inhibited TCA cycle, higher metabolites and bactericidal substances levels. These results collectively revealed that LcHif-1α may promoted the functional activities of head kidney macrophages in protecting hypoxia-tolerant L. crocea from Aeromonas hydrophila infection.